TEORI DAN ISU PEMBANGUNAN - Tampongangoy, Deysi Livy Natalia (HOLISTIK, Journal Of Social and Culture, 2016)
The main study public administration which one dimensions the public policy will relating to the formulation, implementation and evaluation public policy. In the formulation of public policy, public administration officials deeply involved, but the not within the public administration but are in the political. Government the intervening centralistic too much to affairs the community cause the attitudes and behavior each other do not believe between the community and the government, in turn would weaken social capital. In this era of information by sophistication telecom technologies appear a new tendency, the house could be a place of worked so as time together husband and wife and children become more long and possibly more intense. So also the relationship between neighbourhood could more familiar. Growing the residents (civil society) will become social capital. Social capital thrives on citizens, and residents also gives democracy. Social capital must be considered character. Social capital chosen to social capital caused no great disruption. In terms of social character capital could be clearly seen at the elite. As we at together that governance have 3 domain namely: state, businesses and citizens. Keywords: public administration, social capital, policy